Migration and aspirations: Are migrants trapped on a hedonic treadmill? - Mathias Czaika; Marc Vothknecht (IZA Journal of Migration, 2014)
Based on longitudinal information from two waves of the Indonesian Family and Life Survey (IFLS) in 2000 and 2007, we find evidence that migrants are self-selected along higher individual aspirations acquired (or, inherited) before migration. About 70 per cent of aspiration differentials can be explained by factors such as young age, good education, or superior socio-economic background, while the residual seems to be linked to an individual pre-disposition for higher aspirations. However, despite the fact that migration is economically beneficial for most migrants, the migration experience itself seems to further increase economic aspirations, hereby trapping migrants on a "hedonic treadmill".
Keywords: D03; J61; R23; 330; Internal migration; Migration behaviour; Aspirations; Indonesia